Estudio de prefactibilidad para la implementación de una planta productora de bebidas energizantes a base de maca, (Lepidium peruvianum chacon), complementado con frutas exóticas y endulzado en stevia - Vega Cornelio, Jean Pierre (2020)
The present prefeasibility study has as its main objective the establishment of technical, economic, social and market viability for the implementation of a plant producing energy drinks based on maca, sanky, pitahaya and sweetened in stevia in presentations of ecoflex plastic packaging of 300 ml The objective has been determined through analyzes divided into the following chapters: During the first 02 chapters, the general aspects of the project are detailed, through the definition of objectives and hypotheses, with the respective justifications of the case. Likewise, the business sector is analyzed and market attention is defined, which will be 420,280 bottles and 502,889 bottles during the first and last year of operation. In the third and fourth chapter, the analysis is presented regarding the macro and microlocazación of the plant and the size of the same, which will be installed in Metropolitan Lima, province of Metropolitan Lima, district of San Juan de Lurigancho and have a capacity of 502,889 bottles or 150,866.85 liters, without presenting limitations in inputs or technology, since resources and machines can be easily acquired. In the fifth chapter, the engineering of the project is defined, where the flow of the productive process and necessary resources (machines, operators) are presented. On the other hand, analyze the key factors, stories such as quality, safety and health at work and associated environmental impacts, in addition to the calculation for obtaining the various areas within the plant. In addition, in the sixth chapter, see details of the structure of the company, after defining the mission, vision and values. It also details the specific functions of each job. Finally, the last 02 chapters refer to the calculation of the investment and financial and social results of the study. An investment of 661,766 soles, tangible assets, intangibles and working capital has been estimated. The results of the study had a demand of 420,280 bottles and 502,889 bottles during the first and last year of operation, representing an economic NPV and IRR of 196,524 soles and 21.15%, in addition to a financial NPV and IRR of 275,279 soles and 46, 95%, in addition to 36,765 soles as capital density.